Cloning and expression of the HN gene from the velogenic viscerotropic Newcastle disease virus strain AF2240 in Sf9 insect cells - Ong, H. K. A.; Ali, A. M.; Omar, A. R.; Yusoff, K. (Springer Science and Business Media LLC, 2000)
The haemagglutinin-neuraminidase (HN) gene of Newcastle disease virus (NDV) strain AF2240, amplified from the viral genomic RNA (~1.8 kb) was directionally cloned and inserted into a baculovirus expression vector system. The recombinant glycoprotein expressed in Spodoptera frugiperda (Sf9) cells showed haemagglutinin (HA), neuraminidase (NA) and hemadsorption activities. HA activity was detected in both extra- and intra-cellular recombinant HN (recHNAF2240) samples. In addition, both HA and hemadsorption activities were inhibited by polyclonal anti-NDV sera. Furthermore, significant expression of the recombinant protein was observed on the surface of infected cells. SDS-PAGE analysis revealed the presence of visually distinguishable bands between the 70 and 80 kDa in size that were absent in the wild-type samples. Western blot analysis showed that the distinct ~63 kDa band and a ~75 kDa band corresponded to the unglycosylated and glycosylated HN glycoprotein respectively as reported in another study. These observations indicated that the HN recombinant protein was not only expressed on the surface of the infected cells as well as with the viral coat protein, but also appears to be functional.